Keteguhan Rekat Terkoreksi Sebagai Pengendali Mutu Kayu-Lapis Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT Plywood which is a main product and/or export commodity of forestry industry sector needs to be reviewed its quality control procedures. There are so many procedures to be followed that product quality control process becomes confusing and annoying, uninteresting. For that reason, it needs a new, easier procedure for increasing their interest. Twelve panels were purchased for this purpose. All quality control measures were recorded and tested against SKI and SII and other procedures. They were physical dimension and glue-line strength. The first consisted of length, width, thickness, squareness of the panel dimension, specific gravity, dimension stability and static bending of the panel. The second covered glue-line strength at both air-dry and wet testing condition and percentage of wood failure. The corrected glue-line strength was calculated by multiplying glue-line strength and its respective percentage wood failure at both testing condition. The results showed that only 66.7% of tested panels were in conformation with JAS. This value decreased to 33.3% when second panel 's measure (percentage wood failure) were incorporated. On the other hand, corrected glue-line strength could increase up to 41.7% which is bigger value than the existing results of SD and SKI product quality controlling procedure.